PENGARUH IKLIM ORGANISASI DAN KECERDASAN EMOSIONAL TERHADAP MOTIVASI KERJA KARYAWAN PT. BENUA NUSA INDONESIA MEDAN - Theresia Cuangnita; Syawaluddin Syawaluddin; Elcy Handayani Pramita; Thomas Sumarsan Goh (STIE Wiyatamandala, 2023)
The purpose of this study aims to test and analyze the influence of Organizational Climate and Emotional Intelligence on Work Motivation at PT. Benua Nusa Indonesia Medan. This method research uses descriptive quantitative research with 64 respondents of the total population. Multiple linear regression analysis, partial and simultaneous hypothesis testing, also the test of coefficient determination (R2) are used in data analysis methods. The conclusion from the results of this study is that Organizational Climate and Emotional Intelligence has a significant effect on employee Work Motivation at PT. Benua Nusa Indonesia Medan.